Rhythmic Learning Method on Drumband Music for Children a Kindergarten in Early Childhood Islam Tunas Harapan Salatiga - Wardani, Indah; Nugroho, R. Agustinus Arum Eka (Jurusan PGPAUD FIP UNNES, 2018)
Learning music in kindergarten now experiencing rapid development, seen from the many music competitions in various categories. Learning music in a group that is often used for children's competition in which music Drumband because it has some benefits. By joining the race to make every kindergarten has its own methods to train their students. It also occurs in early childhood music education in the city of Salatiga. This study aims to explain the learning method Drumband rhythmic music for kindergarten children A, factor inhibitors and rhythmic in early childhood learning support Islam Tunas Harapan Salatiga. This study uses descriptive qualitative method. Research subjects in this study was the coach Drumband Islam Tunas Harapan early childhood and early childhood Principal Islam Tunas Harapan Salatiga. The validity of the data using triangulation techniques. The data analysis was done of data collection techniques, data reduction, data presentation and conclusion. Results obtained from this study is the learning method Drumband rhythmic music to children in early childhood kindergarten A Islam Tunas Harapan Salatiga is the method of demonstration, imitation method and method drill. The method used coach interrelated and complementary. Coaches use strategies that prevent children tired and bored and alternated every meeting. Factors supporting the rhythmic music Drumband learning for kindergarten children in early childhood A Islam Tunas Harapan Salatiga is coaches, principals and teachers. Factors inhibiting learning Drumband rhythmic music for kindergarten children A, namely infrastructure and creativity